Practices of Digital Citizenship Among Female Secondary School Students in Riyadh City - Al-Shamhani, Manal Mohammad; Al-Majed, Maram Abdulrahman; Al-Garni, Noura Mohammad (Journal of Curriculum and Teaching Methodology, 2025)
The aim of the study was to explore the digital citizenship practices among female secondary school students in Riyadh. The study sample consisted of 301 female secondary school students. To achieve the study objectives, a descriptive approach was used, and a questionnaire consisting of 37 items was developed, covering three main areas: respect, learning and communication, and protection. The results showed that the participants exhibited a high level of awareness and commitment to digital citizenship practices across its various aspects. The overall mean score for the areas was 4.29, with the "Respect" area ranking first with a mean score of 4.56, indicating it was the most important for the participants compared to the other areas. The "Learning and Communication" area ranked third with a mean score of 4.17, suggesting it was relatively less important despite receiving a positive evaluation. Overall, the results indicated that the study participants highly value human values such as respect and protection, while giving less importance to learning and communication. Based on the results, the study recommends encouraging teachers to discuss digital citizenship practices with learners to enhance critical thinking and increase awareness of freedom of expression and digital well-being. It also recommends fostering a sense of responsibility and collaboration with parents, encouraging them to support and promote digital citizenship at home by offering workshops on how to protect their children online and encourage proper digital behavior. These behaviors should become a way of life and part of their personalities. Additionally, the study suggests incorporating laws and penalties issued by government agencies in learning platforms such as "Madrasati." It also recommends implementing Digital Citizenship Weeks in schools through practical activities, interactive sessions, or community involvement to raise awareness of digital values among students, teachers, and parents. Lastly, the study encourages sharing the results and activities of Digital Citizenship Week via school social media platforms.
Keywords: Practices; Digital Citizenship; High School Stage